Retesting the Hypothesis of a Clinical Randomized Controlled Trial in a Simulation Environment to Validate Anesthesia Simulation in Error Research (the VASER Study). (March 2017) - Merry, Alan F.; Hannam, Jacqueline A.; Webster, Craig S.; Edwards, Kylie-Ellen; Torrie, Jane; Frampton, Chris; Wheeler, Daniel W.; Gupta, Arun K.; Mahajan, Ravi P.; Evley, Rachel; Weller, Jennifer M.
Abstract : Background: Simulation has been used to investigate clinical questions in anesthesia, surgery, and related disciplines, but there are few data demonstrating that results apply to clinical settings. We asked "would results of a simulation-based study justify the same principal conclusions as those of a larger clinical study?" Methods: We compared results from a randomized controlled trial in a simulated environment involving 80 cases at three centers with those from a randomized controlled trial in a clinical environment involving 1, 075 cases. In both studies, we compared conventional methods of anesthetic management with the use of a multimodal system (SAFERsleep ® ; Safer Sleep LLC, Nashville, Tennessee) designed to reduce drug administration errors. Forty anesthesiologists each managed two simulated scenarios randomized to conventional methods or the new system. We compared the rate of error in drug administration or recording for the new system versus conventional methods in this simulated randomized controlled trial with that in the clinical randomized controlled trial (primary endpoint). Six experts were asked to indicate a clinically relevant effect size. Results: In this simulated randomized controlled trial, mean (95% CI) rates of error per 100 administrations for the new system versus conventional groups were 6.0 (3.8 to 8.3) versus 11.6 (9.3 to 13.8; P = 0.001) compared with 9.1 (6.9 to 11.4) versus 11.6 (9.3 to 13.9) in the clinical randomized controlled trial ( P = 0.045). A 10 to 30% change was considered clinically relevant. The mean (95% CI) difference in effect size was 27.0% (−7.6 to 61.6%). Conclusions: The results of our simulated randomized controlled trial justified the same primary conclusion as those of our larger clinical randomized controlled trial, but not a finding of equivalence in effect size. Abstract : This investigation repeated the clinical trial, but in a smaller simulated trial, to determine if the same principal conclusion would be reached as in the actual clinical trial. The small simulated trial reached the same conclusion as the larger clinical trial, but the effect size was different. Caution is needed when extrapolating findings from research in simulated settings to clinical practice.